My Father's War : fighting with the Buffalo Soldiers in World War II - Johnston, Carolyn, 1948- (University of Alabama Press, 2012)
My Father's War tells the compelling story of a unit of black Buffalo Soldiers and their white commander fighting on the Italian front during World War II. The 92nd Division of the Fifth Army was the only African American infantry division to see combat in Europe during 1944 and 1945, suffering more than 3,200 casualties. Members of this unit, known as Buffalo Soldiers, endured racial violence on the home front and experienced racism abroad. Engaged in combat for nine months, they were under the command of southern white infantry officers like their captain, Eugene E. Johnston. Carolyn Ross Johnston draws on her father's account of the war and her extensive interviews with other veterans of the 92nd Division to describe the experiences of a naïve southern white officer and his segregated unit on an intimate level. During the war, the protocol that required the assignment of southern white officers to command black units, both in Europe and in the Pacific theater, was often problematic, but Johnston seemed more successful than most, earning the trust and respect of his men at the same time that he learned to trust and respect them. Gene Johnston and the African American soldiers were transformed by the war and upon their return helped transform the nation.